The Relationship Between Self-Care and Quality of Life in Patients With Coronary Artery Disease in Siloam Hospital Lippo Village - Sunanto Ng; Karin Pratiwi Oktaviani (Medicinus, 2026)
Background: Coronary artery disease not only contributes to high mortality but also substantially impairs quality of life. Although self-care is recognized as a key component of chronic disease management, empirical evidence integrating disease-specific self-care assessment and symptom-based quality of life measurement in Indonesian populations remains limited.   Methods: This analytical observational study employed a cross-sectional design involving 50 outpatients with CAD at Siloam Lippo Village Hospital (June–September 2023). Self-care was assessed using the Self-Care of Coronary Heart Disease Inventory (SC-CHDI), while quality of life was measured using the Seattle Angina Questionnaire (SAQ). Data were analyzed using the Chi-square test with a significance level of p<0.05.   Result: A total of 60% of participants demonstrated good self-care and quality of life. A significant association was observed between self-care and quality of life (p=0.038; OR=4.125; 95% CI: 1.235–13.782). Clinical factors including hypertension (p=0.007), diabetes mellitus (p<0.001), and angina severity grade (p=0.002) were also significantly associated with quality of life.   Conclusion: Self-care is a key determinant of quality of life in patients with CAD. Notably, the use of disease-specific instruments (SC-CHDI and SAQ) provided a more sensitive and clinically relevant assessment of the relationship between self-care behaviors and patient-reported outcomes, supporting the implementation of patient-centered care strategies in clinical practice.